(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
This article presents some reflections on the teaching of art, focusing on the construction of educational materials that were conceived within French semiotic’s theory - individually or collectively by the author. From the conjecture of the two disciplines, art and semiotics, parameters were established for the production of the referred materials, always with the objective of proposing a deepening of the students’ understanding of art, as well as expanding the way of learning and teaching art. Thus, the image reading guided by the theoretical and methodological framework of French semiotics, as will be presented in the article, was the starting point for the production of the materials discussed in this work: “arte br”, the collection “O leitor de imagens” (The image reader), “Eco Arte”, “Todo passado dentro do presente” (All past within the present) and “Arte na Escola” (Arts at school).